Development of Hardboards from Spent Chips of Acacia catechu (Khair) - Shukla, K. S.; Shah, R. S.; Bagga, J. K. (Indian Forester, 1985)
Large quantities of spent chips of Acacia catechu (khair) after extracting katha and cutch from the same are left over in various units engaged in the trade in different parts of the country. This wood raw material has so far not found any economic use except as fuel. In the present paper suitability of khair chips for the manufacture of hardboards is reported. Pulp of optimum quality for developing hardboards was obtained by cooking the chips for 3 hours in water having 3-7 per cent alkali concentration. Flexural strength of the boards improved considerably on heat treatment. Boards meet the requirements of the specification for standard hardbords in all the cases of alkali concentrations. Satisfactory boards were also prepared by mixing spent chips of khair and su-babul (Leucaena leucocephala) in the ratio of 70:30 and 5O:5O using paraffin wax as sizing material in the board formation stage. Such boards did not require any further treatment. Board have smooth feel and appealing look.